A birch sublingual allergy immunotherapy tablet reduces rhinoconjunctivitis symptoms when exposed to birch and oak and induces IgG4 to allergens from all trees in the birch homologous group. Issue 2 (22nd November 2018) - Couroux, Peter; Ipsen, Henrik; Stage, Brian Sonne; Damkjær, Jakob Thomas; Steffensen, Maria Abildgaard; Salapatek, Anne Marie; Lund, Kaare; Würtzen, Peter Adler
Abstract: Background: This randomized, double‐blind trial was conducted to determine the optimal dose for clinical efficacy of the SQ tree SLIT‐tablet. An environmental exposure chamber (EEC) was used to reduce variability of allergen exposure and allow investigation of symptom reduction towards different species from the birch homologous group in separate EEC sessions. Methods: Eligible subjects (N = 219) were randomized to receive treatment with placebo or the SQ tree SLIT‐tablet (2, 7, or 12 DU) for 24 weeks. EEC pollen challenges were conducted outside the birch pollen season and included four birch and two oak EEC sessions. The primary efficacy endpoint was the average allergic rhinoconjunctivitis (ARC) total symptom score (TSS) after 24 weeks of treatment. Results: There was a statistically significantly lower TSS during the 24‐week birch EEC session for 7 DU and 12 DU compared to placebo with relative differences of 24% ( P  = 0.03) and 25% ( P  = 0.02). For the 24‐week oak EEC session, there was a statistically significant difference for 12 DU (24%, P  = 0.03). IgE and IgG4 measurements supported these findings and demonstrated cross‐reactivity to all other species within the birch homologous group. Treatment was well‐tolerated with the most frequently reported adverse reactions being the local reactions in the oral cavity of mild‐to‐moderate severity. Conclusion: This trial demonstrates that the SQ tree SLIT‐tablet reduce ARC symptoms triggered by birch or oak pollen. The optimal dose for further development was 12 DU. Clinical and immunological findings suggest that the tablet may be used to treat allergies to all species within the birch homologous group. Abstract : Treatment with the SQ tree SLIT‐tablet, induced statistically significant reductions of rhinoconjunctivitis symptoms compared to placebo, in birch allergic subjects exposed to birch or oak pollen in an environmental exposure chamber. Statistically significant differences between 12 DU and placebo were reached after 16 weeks treatment and persisted until week 24 (end‐of‐trial). The reduction in rhinoconjunctivitis symptoms during oak pollen exposure, provides proof of concept for clinically relevant therapeutic cross‐reactivity between birch and other trees in the birch homologous group, which was also supported by IgG4 measurements. * P <0.05; SLIT: sublingual allergy immunotherapy tablet; SQ: SQ is a method of standardisation; DU: development unit.